1991
DOI: 10.3109/08990229109144726
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Motor Cortical Neuron Synaptic Terminals on Monkey Parvocellular Red Nucleus Neurons

Abstract: We determined the location of 54 horseradish peroxidase (HRP)-labeled motor cortical neuron synaptic terminals on 17 parvocellular neurons in the monkey red nucleus. Synaptic terminals and their postsynaptic elements were identified and reconstructed, using light- and electron-microscopic techniques, from serial thick and thin sections. Terminals were found on proximal and distal dendrites of small and medium-sized parvocellular neurons, where they formed excitatory synapses. Some were 180 microns from cell so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…It has also been reported in recent work in the turtle (Keifer et al, 1992) and for cortically mediated inhibition of rubral neurons in the cat (Katsumaru et al, 1984) and has been demonstrated with immuno-GABA-gold labeling in RNm in the monkey (Ralston and Milroy, 1992). In a brief electron microscopic study of corticorubral terminals in RNp of one monkey (Jenny et al, 1991), the authors described cortical terminals synapsing upon proximal and distal dendrites of rubral neurons. These authors did not use GABA immunohistochemistry and depicted one cortical axodendritic terminal containing rounded synaptic vesicles but did not report the presence of glomerular relationships of cortical afFerents with dendritic spines, small-diameter dendrites, or psds that are such a prominent finding of the present study.…”
Section: The Cortical Projection and Its Relationship With Local Circsupporting
confidence: 53%
See 1 more Smart Citation
“…It has also been reported in recent work in the turtle (Keifer et al, 1992) and for cortically mediated inhibition of rubral neurons in the cat (Katsumaru et al, 1984) and has been demonstrated with immuno-GABA-gold labeling in RNm in the monkey (Ralston and Milroy, 1992). In a brief electron microscopic study of corticorubral terminals in RNp of one monkey (Jenny et al, 1991), the authors described cortical terminals synapsing upon proximal and distal dendrites of rubral neurons. These authors did not use GABA immunohistochemistry and depicted one cortical axodendritic terminal containing rounded synaptic vesicles but did not report the presence of glomerular relationships of cortical afFerents with dendritic spines, small-diameter dendrites, or psds that are such a prominent finding of the present study.…”
Section: The Cortical Projection and Its Relationship With Local Circsupporting
confidence: 53%
“…These authors did not use GABA immunohistochemistry and depicted one cortical axodendritic terminal containing rounded synaptic vesicles but did not report the presence of glomerular relationships of cortical afFerents with dendritic spines, small-diameter dendrites, or psds that are such a prominent finding of the present study. This discrepancy may be explained by the fact that most interactions of cortical afferents with local circuit neurons take place at the distal dendrites of projection neurons, and Jenny et al (1991) described cortical terminals that were more proximally located.…”
Section: The Cortical Projection and Its Relationship With Local Circmentioning
confidence: 99%
“…Thus, given the cellular distribution of our sample of boutons in the rat, it appears that the more distally located dendritic arbors of rubrospinal neurons receive overlapping inputs from the cerebellum and cerebral cortex, whereas the soma and the most proximally located dendrites receive the cerebellar inputs. This partly overlapping organization of cerebellar and cortical inputs may be similar to that described in monkeys (Jenny et al, 1991; Ralston, 1994a,b) and should be reexamined in other mammals. The cellular localization of the hypothalamorubral projections has not been described previously in any species.…”
Section: Discussionsupporting
confidence: 77%
“…The mammalian red nucleus (RN) processes sensorimotor information from the frontoparietal cortex (Kuypers and Lawrence, 1967; von Monakow et al, 1979; Humphrey et al, 1984; Jenny et al, 1991; Ralston, 1994a; Tokuno et al, 1995; Burman et al, 2000) and the cerebellar cortex (Flumenfelt et al, 1973; Miller and Strominger, 1977; Stanton, 1980; Asanuma et al, 1983; Ralston, 1994a). It transmits the transformed signals back to the cerebellum through the rubroolivary projection to the climbing fiber system (De Zeeuw et al, 1998) and also to the spinal cord through the rubrospinal neuron populations (Eccles et al, 1967; Massion, 1967; Ralston et al, 1988; Keifer and Houk, 1994).…”
mentioning
confidence: 99%